ANALISIS KOMPETENSI DAN PERMASALAHAN DALAM MENULIS ARTIKEL PADA MATA KULIAH MEKANIKA ANALITIK - Mubarokah, Izza Ifada; Mohamad Jahid, Sarah; Setiaji, Bayu (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This research analyzes competencies and problems in writing scientific articles in analytical mechanics courses at the Department of Physics, FMIPA, Yogyakarta State University (UNY). Students from the Physics education study program class of 2022 were the research subjects, with 30 out of 40 students selected as random samples. Qualitative descriptive research methods were used, with data collection through questionnaires. The research results show that the main problem faced by students is difficulty in finding appropriate references and understanding relevant literature, which was expressed by 32.1% of respondents. Further analysis identified students' key strengths, such as good analytical physics skills and access to adequate laboratory facilities, as well as weaknesses such as lack of training in academic writing. Opportunities to overcome these weaknesses include information technology support and collaboration with other institutions, while threats faced include time constraints and academic pressure. This research suggests the need for increased training in literature searching and academic writing as well as the use of technology to expand access to information. With the right strategy, it is hoped that students can improve their competency in writing scientific articles and be better prepared to face academic challenges. These findings provide valuable insights for improving the curriculum and teaching methods at UNY, so as to improve the quality of education and research.